2009
DOI: 10.1111/j.1551-2916.2008.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Nanocrystalline Layer on the Surface of Stone Wool Fibers

Abstract: In the present paper, we report a simple approach for creating a nanocrystalline layer on the surface of stone wool fibers (SWFs) with a basalt-like composition. The approach is based on a preoxidation process of the SWFs in atmospheric air at a temperature around the glass transition temperature (T g ) for various durations. During preoxidation, the network-modifying ions diffuse from the interior toward the surface of SWFs and react with oxygen on the surface to form oxides. This diffusion process is accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Kistler [62] suggested that the bonding of trivalent atoms, such as aluminium, will be less strong, but that those ions that are di-or mono-valent are the most likely to be able diffuse through the glass network. The findings of Yue et al [56] regarding magnesium oxide migration in stone wool fibres would appear to be concurrent with this. Changes in surface concentrations of Mg, Al and Si following sub-T g treatments of magnesium aluminosilicate fibres have been reported [30].…”
Section: Ion Exchangesupporting
confidence: 56%
See 1 more Smart Citation
“…Kistler [62] suggested that the bonding of trivalent atoms, such as aluminium, will be less strong, but that those ions that are di-or mono-valent are the most likely to be able diffuse through the glass network. The findings of Yue et al [56] regarding magnesium oxide migration in stone wool fibres would appear to be concurrent with this. Changes in surface concentrations of Mg, Al and Si following sub-T g treatments of magnesium aluminosilicate fibres have been reported [30].…”
Section: Ion Exchangesupporting
confidence: 56%
“…The levels of GF crystallisation reported on in this work do not seem to have been replicated since. However, a recent study of stone wool fibres [56] has shown evidence of a surface nano-crystallisation phenomenon involving periclase (MgO) crystals. Whether these findings have relevance to the thermal recycling of E-glass fibres is uncertain.…”
Section: Crystallisationmentioning
confidence: 99%
“…Oxidation of ferrous (Fe 2+ ) to ferric (Fe 3+ ) iron causes outward diffusion of divalent cations (such as Mg 2+ and Ca 2+ ) from the interior of the glass towards the surface. The oxidation process at temperatures near T g does not cause oxygen to diffuse into the interior of samples, instead, it causes the flux of electron holes (h ) into the interior via the reaction Fe 2+ + h = Fe 3+ [8][9][10][11][12][13][14][15][16]. The driving force (Gibbs free energy of the redox reaction) is gradually dissipated by the electron holes.…”
Section: Introductionmentioning
confidence: 98%
“…The surface of iron-bearing silicate glasses can be modified by oxidizing them around T g [8][9][10]. Oxidation of ferrous (Fe 2+ ) to ferric (Fe 3+ ) iron causes outward diffusion of divalent cations (such as Mg 2+ and Ca 2+ ) from the interior of the glass towards the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of polyvalent element-bearing silicate glasses, in particular the investigation of cation diffusion due to heat-treatments in different atmospheres, comprehensive work was done by Smedskjaer and co-workers [26][27][28][29]. The authors observed the formation of nano layers and reported that the morphology and elemental concentration profiles are strongly influenced by the atmosphere used [26].…”
Section: Introductionmentioning
confidence: 99%